Supply Chain Management for Value Added In Agriculture Sector of Indonesia - Hadi Setiawan; Sofia Arie Damayanty; Rita Helbra Tenrini (International Journal of Supply Chain Management, 2020)
Abstract— macroeconomic aspects of preferred value chains. This paper introduces the concept of SCM and illustrates its applications in agroindustries, with a focus on Value Added Tac (VAT) in Indonesia. VAT is one of the main sources of tax revenue in Indonesia, which is a percentage applied to the sale price charged for goods or services at every point in the supply chain. Currently, the tax revenue is one of the fiscal risks that must be mitigated by the Government, since it never reached the target in the last ten years except in 2008. One discourse being raised to increase tax revenue is to charge VAT on all goods and services, including the agriculture sector. This paper uses the latest of Indonesian social accounting matrix (SAM) multiplier model to quantify the economic impact of the supply chain system for imposition of VAT on the agriculture sector. The overview of agriculture value chain in Indonesia was done and supply chain risk management and logistics cost were described. Then, the recommendation was provided for optimizing the agricultural value chain. The results is the imposition of VAT on agricultural sector in all supply chains will give a positive impact if all VAT revenue distributed to the poor